Draft Annual Plan 1994-1995 Volume-II Details of Schemes Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1994)
Increasing intensity is the only strategy increasing production in the Island's since the area expansion is not permissible. The Expert Committee of ICAR have also, recommended for increasing the cropping intensity of the paddy land in these Islands by putting the maximum area under Minor Irrigation during the last few five year plans.
Andaman and Nicobar Administration